Margaret Chase Smith Essay: The Urgency of Democracy - Adams, William (Maine Policy Review, 2015)
In primary and secondary schools in Maine and across the country, classroom time devoted to civics and American political history, along with many humanities subjects, is under increasing pressure. William D. Adams argues that failure to teach these subjects is related to a decline in meaningful political participation and civic engagement of all kinds in the United States. He draws connections between a healthy democracy and democratic citizenship and the ability to think critically, to imagine alternatives, to advance the common good, and to feel empathy and respect for others that a robust humanities education encourages.